2005
DOI: 10.1111/j.1600-0838.2004.407.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity on urinary leakage in primiparous women

Abstract: The impact of physical activity on urinary leakage (UL) has previously been considered, but not in relation to first pregnancy and delivery. The aim of this study was to describe physical activity and urinary leakage before, during and after the first childbirth. The subjects who were invited to participate in the study were taken consecutively from nine maternity clinics in the northwest part of Stockholm County, and the study group included 665 primiparous women. The mean age of the women was 28 (range 17-43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 31 publications
2
57
1
10
Order By: Relevance
“…57 Other potential benefits of resistance training include better posture, prevention of gestational low back pain and diastasis recti, and strengthening of the pelvic floor. 58,59 Limitations of this study include the fact that we did not record detailed information about dietary habits. However, it is unlikely that this had a major influence on the results because both groups of women were well nourished, ate to appetite, and had similar weight gain during pregnancy, and also similar BMI before pregnancy and before delivery.…”
Section: Discussionmentioning
confidence: 99%
“…57 Other potential benefits of resistance training include better posture, prevention of gestational low back pain and diastasis recti, and strengthening of the pelvic floor. 58,59 Limitations of this study include the fact that we did not record detailed information about dietary habits. However, it is unlikely that this had a major influence on the results because both groups of women were well nourished, ate to appetite, and had similar weight gain during pregnancy, and also similar BMI before pregnancy and before delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish study, women who engaged in low-impact physical activity reported improved urinary continence. 24 In the DPP, women randomized to the lifestyle intervention group reported a reduction in rates of stress incontinence, mostly due to changes in weight. Of note, rates of incontinence were seen to be as high as 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Eliasson found an identical incidence of UI 12 months postpartum among 665 Swedish primiparous women (Eliasson et al, 2005). In a smaller Danish cohort of 305 primiparous women Viktrup et al found an incidence of stress UI of 7 % 3 months after vaginal delivery (Viktrup et al, 1992).…”
Section: Incidence Of Urinary Incontinence Postpartummentioning
confidence: 91%